Bone-targeting AAV-mediated silencing of Schnurri-3 prevents bone loss in osteoporosis - Yang, Yeon-Suk (Nat Commun, 2019)
RNAi-based bone anabolic gene therapy has demonstrated initial success, but many practical challenges are still unmet. Here, we demonstrate that a recombinant adeno-associated virus 9 (rAAV9) is highly effective for transducing osteoblast lineage cells in the bone. The adaptor protein Schnurri-3 (SHN3) is a promising therapeutic target for osteoporosis, as deletion of shn3 prevents bone loss in osteoporotic mice and short-term inhibition of shn3 in adult mice increases bone mass. Accordingly, systemic and direct joint administration of an rAAV9 vector carrying an artificial-microRNA that targets shn3 (rAAV9-amiR-shn3) in mice markedly enhanced bone formation via augmented osteoblast activity. Additionally, systemic delivery of rAAV9-amiR-shn3 in osteoporotic mice counteracted bone loss and enhanced bone mechanical properties. Finally, we rationally designed a capsid that exhibits improved specificity to bone by grafting the bone-targeting peptide motif (AspSerSer)(6) onto the AAV9-VP2 capsid protein. Collectively, our results identify a bone-targeting rAAV-mediated gene therapy for osteoporosis.